ESTABLISHMENT AND EVALUATION OF ORTHOTOPIC HEPATOCELLULAR CARCINOMA AND DRUG-INDUCED HEPATOCELLULAR CARCINOMA IN MICE WITH SPLEEN-DEFICIENCY SYNDROME IN TRADITIONAL CHINESE MEDICINE - Luo, Haoxuan; Chen, Yan; Sun, Baoguo; Xiang, Ting; Zhang, Shijun (African Journal of Traditional, Complementary and Alternative Medicines, 2016)
Background: Spleen-deficiency syndrome (SDS) in Traditional Chinese Medicine (TCM) played pivotal roles on the development of hepatocellular carcinoma (HCC). This study was performed to establish and evaluate HCC model in mice with SDS in TCM. Material and Methods: A total of 90 C57BL/6 mice were randomized in six groups (n=15 for each group): A, Control group; B, SDS group; C, orthotopic HCC (OHCC) group; D, OHCC based on SDS (SDS-OHCC) group; E, Druginduced HCC (DHCC) group; F, DHCC based on SDS (SDS-DHCC) group. The SDS model were established by subcutaneous injection of reserpine, followed by the OHCC or DHCC model establishment. The SDS scores, tumor formation rate and survival time were recorded and calculated, as well as the histochemical stain was performed. Results: The SDS scores of mice in Group B, D, F were 17.57±4.86 (P<0.05 vs. Group A), 18.13±4.53 (P<0.05 vs. Group A and C) and 23.32±4.94 (P<0.05 vs. Group A and E) respectively. The tumor formation rate of mice in Group C, D, E and F were 73.33%, 100%, 60% and 80% respectively. The survival time of mice in Group C, D, E and F were 26.42±5.27, 17.33±4.76 (P<0.05 vs. Group C), 35.77±6.12 and 22.61±5.05 (P<0.05 vs. Group E) respectively. Conclusion: The SDS-oriented HCC mice models were simple and easily-operated models for further studies on SDS oriented tumor. Meanwhile, SDS was a pivotal factor for low outcome of hepatic tumor.